Estudo teórico das propriedades estruturais, eletrônicas e vibracionais de pontos quânticos de silício e grafeno e cálculos no formalismo DFT aplicados a cristais de ácido úrico - Silva, Agmael Mendonça (2010)
There is a great interest in understanding the electronic properties of nano-structured materials aiming the development of new nano devices, especially how to modify the electronic properties of nano structures already known in a controlled manner. This work shows our studies, which were made in a pure atomistic way by computational simulation, on the electronic, optical and vibrational properties of (a) spherical quantum dots, silicon solid and hollow ones, (b) graphene nanoflakes and (c) crystals of uric acid, anhydrous, mono and dihydrate ones, using methods of Molecular Dynamics, Semiempirical, DFTB+ and DFT. We used the software called AMPAC and the modules of Materials Studio (Accelrys), the Forcite, CASTEP, Gulp and Dmol3 that are states of art in atomistic simulations. From the classical point of view we used Brenner force fields, which allow the formation and breaking of covalent bonds; and from the quantum dots of view, we used the method of density functional and DFTB+. In the study of silicon quantum dots, it was obtained a decrease of the energy gap due to the increase of the radius for massive dots, and contrary behavior to the hollow dots, when we fixed one point and varied only the radius of the hole. In relation to the graphene nanoflakes, it was obtained the stability of structures by the Dynamics Molecular, verifying that they keep their flattened form up to 1000 K; over 3400 K structures begin to have their links broken. The HOMO-LUMO energy gaps are sensitive to edges. Analysis of spin states revealed that only the triangular nanoflakes with zigzag edge have excess of electrons with α spin, however symmetry dependent. The modes of vibration for structures with nC ∼ 50 were obtained and it was observed that rectangular nanoflake displays absorption bands in common with zigzag nanoflakes in two ranges of the infrared spectrum. Finally for the uric acid crystals, we observed that the lattice parameters for the dihydrate crystal are less consistent with experimental values. The gap of the crystal of uric acid, anhydrous and mono ones, is direct (∼ 3.18 eV and 3.16 eV, respectively) and of the dihydrate is indirect (∼ 2.89 eV). The 2p orbitals are the largest contributors to the density of states. Water has great influence in the conduction band of the dihydrate crystal. There is an anisotropic behavior in relation to the study of the optical properties of these crystals along four directions of incidence of the electric field, where the anisotropy is more accentuated to the dihydrate. The studies fit in the theme of the role of Instituto de NanoBioEstruturas & Simulação NanoBioMolecular [NANO(BIO)SIMES], one of the National Institutes of Science and Technology funded by CNPq from the beginning of 2009, which aims to develop research activities and high-quality human resource training in nanobiostructures and nanobiomolecular simulation.